Blue honeysuckle (Lonicera caerulea subsp. edulis (Turcz. ex Herder) Hultén.) berries and changes in their ingredients across different locations. (28th February 2018) - Senica, Mateja; Bavec, Martina; Stampar, Franci; Mikulic‐Petkovsek, Maja
Abstract: BACKGROUND: Interest in organic blue honeysuckle berries has increased in recent years. They are rich in various health‐promoting compounds which are sensitive to different environmental factors and are modified during the growing season. RESULTS: Honeysuckle berries from different locations differed significantly in their contents of primary and secondary metabolites. The location Ogulin, with the highest altitude and consequently high UV radiation, had the highest phenolic content (259.85 mg per 100 g). Additionally, Vukovski Vrh, with the lowest temperature, had the highest ascorbic acid content (36.83 mg per 100 g), while Šmartno pri Litiji and Višnja Gora, with the highest precipitation, had the highest organic acid contents (885.85 and 850.01 mg per 100 g respectively). A combination of stressful environmental conditions of temperature, water source and light intensity led to the highest saponin content in Višnja Gora (695 mg per 100 g), the highest tannin content in Dolnje Impolje (134 mg per 100 g) and the highest sugar content (2585.45 mg per 100 g) in Vučetinac. CONCLUSION: The contents of bioactive substances were influenced by various environmental factors such as temperature, UV radiation, altitude, light intensity and fruit ripening stage. Different compounds respond distinctly to different environmental factors. © 2017 Society of Chemical Industry